Psychedelic treatments for mental health conditions pose challenges for informed consent - Seybert, Carolina (2023)
Funding Information: C.S. received payment from the European Monitoring Centre for Drugs and Drug Addiction. A.M.P. received payment or honoraria from Janssen and Lundbeck and participated in advisory boards for Janssen and Angelini. A.J.O.-M. was the national coordinator for Portugal of trials for treatment-resistant depression of psilocybin, sponsored by Compass Pathways, Ltd (EudraCT number 2017-003288-36), and of esketamine, sponsored by Janssen-Cilag, Ltd (EudraCT NUMBER: 2019-002992-33); received payment or honoraria from MSD, Neurolite AG, Janssen and the European Monitoring Centre for Drugs and Drug Addiction; participated in advisory boards for Janssen and Angelini; and is the recipient of a grant from Schuhfried GmBH. The remaining authors declare no competing interests. Funding Information: We thank C. E. Fisher and J. Taborda da Gama for comments on an initial version of this manuscript. This work was supported by grant PTDC/MED-NEU/31331/2017 from the Fundação para a Ciência e Tecnologia to C.S., G.C. and A.J.O.-M. A.J.O.-M. received other grants from the Fundação para Ciência e Tecnologia (PTDC/SAU-NUT/3507/2021; PTDC/MED-NEU/1552/2021) and the Fundação para Ciência e Tecnologia and FEDER (PTDC/MED-NEU/30845/2017_LISBOA-01-0145-FEDER-030845; PTDC/MEC-PSQ/30302/2017_LISBOA-01-0145-FEDER-30302), a Starting Grant from the European Research Council (grant agreement no. 950357) and grants from the European Union’s Horizon 2020 research and innovation program (H2020‑SC1‑2017‑CNECT‑2‑777167‑ΒΟUNCE; H2020‑SC1‑DTH‑2019‑875358‑FAITH) and the European Joint Programme in Rare Diseases (Joint Translational Call 2019) through the Fundação para Ciência e Tecnologia (EJPRD/0001/2020).